Hepatic methionine homeostasis is conserved in C57BL/6N mice on high-fat diet despite major changes in hepatic one-carbon metabolism. - Christoph Dahlhoff (Public Library of Science (PLoS), 2013)
Obesity is an underlying risk factor in the development of cardiovascular disease, dyslipidemia and non-alcoholic fatty liver disease (NAFLD). Increased hepatic lipid accumulation is a hallmark in the progression of NAFLD and impairments in liver phosphatidylcholine (PC) metabolism may be central to the pathogenesis. Hepatic PC biosynthesis, which is linked to the one-carbon (C1) metabolism by phosphatidylethanolamine N-methyltransferase, is known to be important for hepatic lipid export by VLDL particles. Here, we assessed the influence of a high-fat (HF) diet and NAFLD status in mice on hepatic methyl-group expenditure and C1-metabolism by analyzing changes in gene expression, protein levels, metabolite concentrations, and nuclear epigenetic processes. In livers from HF diet induced obese mice a significant downregulation of cystathionine β-synthase (CBS) and an increased betaine-homocysteine methyltransferase (BHMT) expression were observed. Experiments in vitro, using hepatoma cells stimulated with peroxisome proliferator activated receptor alpha (PPARα) agonist WY14,643, revealed a significantly reduced Cbs mRNA expression. Moreover, metabolite measurements identified decreased hepatic cystathionine and L-α-amino-n-butyrate concentrations as part of the transsulfuration pathway and reduced hepatic betaine concentrations, but no metabolite changes in the methionine cycle in HF diet fed mice compared to controls. Furthermore, we detected diminished hepatic gene expression of de novo DNA methyltransferase 3b but no effects on hepatic global genomic DNA methylation or hepatic DNA methylation in the Cbs promoter region upon HF diet. Our data suggest that HF diet induces a PPARα-mediated downregulation of key enzymes in the hepatic transsulfuration pathway and upregulates BHMT expression in mice to accommodate to enhanced dietary fat processing while preserving the essential amino acid methionine.